PENYEBARAN CACING PARASITIK PADA IKAN KEMBUNG PEREMPUAN (Rastrelliger brachysoma) DI PULAU JAWA - Forcep Rio Indaryanto; Yusli Wardiatno; Risa Tiuria (Jurnal Perikanan dan Kelautan, 2014)
Helminth is one of the many parasitic groups found on the body of the fish. The helminth parasitic can inflict harm ecologically, biologically and economically. Monitoring of the distribution of disease in fish is crucial especially when the fish has a pattern of migration from one place to another. Fish sampling was carried out in September – October 2012 from the place of landing of Fishes (TPI), i.e. TPI's Pelabuhan Ratu (West Java province), TPI Karangantu (Banten Province), TPI Bandar Lampungprovince of Bandar Lampung), TPI Muara Angke (DKI Jakarta), and TPI BanyuwangiEast Java province). As many as 160 of 218 R. brachysoma (a prevalence 73.38 %), and number of intencity is 1.378 ± 11.96. The helmint parasitic is a Lechitocladium angustiovum (Digenea: Hemiuridae), Lecitochirium sp. (Digenea: Hemiuridae), Prodistomum orientalis (Digenea: Lepocreadiidae) and Anisakis typica (Nematodes: Anisakidae). Differences in characteristics of R. brachysoma habitat will cause differences in the amount, intensity and prevalence of the helminth parasitic species investment in an area. This is related to the behavior of eating and food availability of R. brachysoma. The distribution of the helminth parasitic in the digestive organs is on intestine (13.72%) and stomach (86.28%), utilizing the existing nutrients as food. In very small amounts, the relationship between the parasite and its host is a mutually beneficial symbiotic relationship but in great numbers, the helminth parasitic infection can lead to secondary infections on the infected organs and can lead to decreased metabolism.Keyword: distribution, helminth parasites, short body mackerel, Jawa Sea, Rastrelliger brachysoma